Electronic design and signal processing - Shama, Kumara; Nayak, K. Prabhakar; Bhat, Somashekara (Narosa Publishing House, 2012)
Electronic Design and Signal Processing discusses in 97 chapters state-of-the-art on: Biomedical Biosensor, Bio-MEMS/NEMS Digital Watermarking Techniques Biometrics, Computer Vision and Pattern Recognition Computer Networks and Sensor Networks Embedded Systems Neural Networks and Fuzzy Logic Network Security Digital Image Processing Signal Processing The book will be useful for undergraduate and postgraduate students, Researchers and Scientists.